Research perspectives in ecodesign. (2020) - Kim, Harrison; Cluzel, François; Leroy, Yann; Yannou, Bernard; Yannou-Le Bris, Gwenola
Abstract : Ecodesign has gained significant traction in recent years ranging from academic research to business applications at a global scale. Initial emphasis on the environmental aspect of design has evolved to include economic and social aspects, with projects ranging from small-scale products to large-scale industrial systems. In this paper, the authors re-analyse 10 of their major ecodesign research projects of the past ten years to identify five categories of challenges and promising future directions for ecodesign research. This paper is primarily a retrospective position paper based on the authors' experience of actual design studies, providing also a relevant literature review and summary of design practices.